Painful, Tender Loin Mass is an Atypical Presentation of Perforation of Retrocaecal Appendix - A Case Reoirt (Bangladesh Medical Journal, 2019)
Right painful, tender loin mass is an unusual presentations of acute appendicitis that arises difficulty in surgical practice. This "case of  right painful, tender loin mass results from perforation of retrocaecal appendix with known case of diabetes mellitus patient 50 years old age. This case facilitates the significance of contrast for abdominal computerized tomography scan for critically ill patient.Bangladesh Med J. 2018 Jan; 47 (3): 41-43